Comparative Study of 2 Surgical Procedures for Osteoporotic Delayed Vertebral Collapse. Issue 2 (15th January 2015) - Nakashima, Hiroaki; Imagama, Shiro; Yukawa, Yasutsugu; Kanemura, Tokumi; Kamiya, Mitsuhiro; Deguchi, Masao; Wakao, Norimitsu; Sato, Takashi; Matsuzaki, Kei; Yoshida, Go; Matsuyama, Yukihiro; Ishiguro, Naoki; et al.
<x xml:space="preserve">Abstract</x> Study Design. Retrospective comparative study. Objective. To compare the surgical results of anterior and posterior combined surgery (AP) and posterior fixation with vertebroplasty (VP) for treating osteoporotic delayed vertebral collapse. Summary of Background Data. The optimal treatment of osteoporotic delayed vertebral collapse has been controversial. Because of aged patients' numerous comorbid medical complications and frequent instrumentation failure secondary to osteoporosis, it is challenging for surgeons to manage osteoporotic delayed vertebral collapse. In spite of this, there have been few reports comparing the surgical results. Methods. A total of 93 patients with osteoporotic delayed vertebral fracture who underwent spinal surgery were enrolled at 6 hospitals. Sixty-five patients underwent AP surgery in 3 hospitals, and 28 patients underwent VP surgery in the other 3 hospitals. We restricted the spinal-fracture level to thoracolumbar lesion (T10–L2) and excluded patients followed up more than 2 years after surgery. The final numbers of patients included in this study were 24 in the AP group and 21 in the VP group. There were no significant differences between the 2 groups in terms of age, sex, disease duration, or duration of follow-up. Results. Operative time was significantly longer and intraoperative blood loss significantly greater in the AP group. No significant difference between the 2 groups was observed in neurological improvement or the angle of kyphosis correction. However, the loss of correction was significantly greater in the VP group. There were no significant differences in perioperative respiratory or other complications. Implant-related complications and pseudarthrosis were more often observed in the VP group. One patient in the VP group underwent additional surgery for progression kyphosis. Conclusion. AP surgery provides stable spinal fixation and reduces implant failure particularly at the thoracolumbar junction because of load bearing of anterior spinal elements. Surgery-related complications in AP surgery were as few in number as with the VP group, and AP surgery is useful for osteoporotic delayed vertebral fracture. Level of Evidence: 3